The mechanism of nitride phases formation at burning of metal powders in air; The 6th International Forum on Strategic Technology (IFOST-2012), Aug. 22-24, 2011 - Kwon Y.-S.; Ilyin A. P. Aleksandr Petrovich; Root L. O. Lyudmila Olegovna; Tikhonov D. V. Dmitry Vladimirovich; Zvjagintseva E. S.; Shinkevitch E. V. (2011, 2011)
Title screen